1997
DOI: 10.1097/00005392-199707000-00069
|View full text |Cite
|
Sign up to set email alerts
|

A Nonsurgical Approach to the Treatment of Phimosis: Local Nonsteroidal Anti-Inflammatory Ointment Application

Abstract: Nonsteroidal anti-inflammatory ointment application for phimosis may be an alternative to surgery and steroid application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 7 publications
0
18
1
5
Order By: Relevance
“…Two studies have noted success with the application of clobetasol propionate cream and described success rates of 89 and 70%, respectively [11, 12]. One study reported a success rate of 75% using a nonsteroidal anti–inflammatory ointment (diclofenac sodium) [13]. In these reports no side effects had been noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have noted success with the application of clobetasol propionate cream and described success rates of 89 and 70%, respectively [11, 12]. One study reported a success rate of 75% using a nonsteroidal anti–inflammatory ointment (diclofenac sodium) [13]. In these reports no side effects had been noted.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid these complications and the discomfort after surgery, a more conservative approach to phimosis has been advocated in several recent studies which support the use of topical creams containing estrogen, steroids or nonsteroidal anti–inflammatory agents applied to the prepuce. Success rates from 67 to 95% have been reported [5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. We present our experience with topical 0.05% clobetasol propionate cream for phimosis in boys.…”
Section: Introductionmentioning
confidence: 94%
“…Neben operativen Korrekturen wurden auch konservative Therapiestrategien (lokal und systemisch), vorrangig lokale Salbenbehandlungen mit steroidalen und nicht-steroidalen antiphlogistischen Wirkstoffen mit unterschiedlichem Erfolg beschrieben [2,7,13,15]. In mehreren Arbeiten wird auf die Effektivität von Betamethason eingegangen, aktuell behandelten Monsour et al [15] 16/25 (64%) Jungen erfolgreich mit einer 0,05%-igen Betamethasonsalbe (Applikation 2-mal täglich).…”
Section: Konservative Alternativenunclassified
“…Allerdings war die Placebobehandlung bereits bei 7/14 (50%) Jungen erfolgreich. Auch mit einer kommerziell nicht erwerbbaren Salbe, die Diclofenac [2] enthielt, wurden 24/32 Jungen von Gökçay et al erfolgreich behandelt. Eine bis zu 90%-ige Erfolgsrate wurde nach lokal hormoneller Salbentherapie mit Oestrogenen beschrieben [16] und eine 95-%ige Erfolgsrate nach simultaner Verabreichung von HCG parenteral und Corticoidsalbe lokal [12].…”
Section: Konservative Alternativenunclassified
“…Since then, several authors have presented results varying from 67% to 95% of sucess, independently of the patients' age. The most common used topical treatments were betamethasone, clobetasol, diclofenac sodium, mometasone furoate 0.05% and triamcinolone acetate (10,12,13). Recent randomized prospective studies have confi rmed that topical use of corticosteroids as treatment for phimosis is superior to placebo (14,15).…”
Section: Introductionmentioning
confidence: 99%